Extreme fluctuations in ambient salinity select for bacteria with a hybrid “salt-in”/”salt-out” osmoregulation strategy - Ionescu, Danny; Zoccarato, Luca; Cabello-Yeves, Pedro J.; Tikochinski, Yaron (Frontiers in Microbiomes, 2024)
Abundant microbial biofilms inhabit underwater freshwater springs of the Dead Sea. Unlike the harsh (over 35 % total dissolved salts) yet stable environment of the basin, the flow rate of the springs changes with random amplitude and duration, resulting in drastic shifts in salinity, pH and oxygen concentrations. This requires the organisms to continuously adapt to new environmental conditions. Osmotic regulation is energetically expensive therefore, the response of the biofilm-organisms to rapid and drastic changes in salinity is interesting. For this purpose, we studied the metagenome of an enrichment culture obtained from a green biofilm covered rock positioned in a spring. We obtained metagenome assembled genomes (MAGs) of Prosthecochloris sp. (Chlorobiales), Flexistipes sp. (Deferribacterales), Izemoplasma (Izemoplasmatales), Halomonas sp. (Oceanospirillales), and Halanaerobium (Halanaerobiales). The MAGs bear genes for both the energetically cheaper "salt-in" and more expensive "salt-out" strategies. We suggest that the dynamic response of these bacteria utilizes both osmoregulation strategies, similar to halophilic Archaea. We hypothesize that the frequent, abrupt, and variable-in-intensity shifts in salinity, typical of the Dead Sea spring system, select for microorganisms with scalable adaptation strategies.